Training on the use of information technology-based media for teachers at Sangkhom Islam Wittaya School, Thailand - Abdul Ngafif; Teguh Wibowo; Tusino Tusino (Community Empowerment, 2024)
The primary objective of this community service activity was to enhance the teachers' capabilities in creating offline-accessible technology-based teaching materials at Sangkhom Islam Wittaya School, Thailand. The lack of experience in developing technology-based teaching materials served as the impetus for this program. A combination of theory and practice was employed throughout the three-stage training and mentoring process: preparation, implementation, and evaluation. Twelve partner teachers participated in the training, which focused on Canva video and Kahoot. Evaluation results indicated that 83% of participants agreed that the training provided a positive learning experience, 92% agreed that the training materials could be used in teaching, 92% agreed that the training enhanced their professionalism, 75% agreed that their projects could be shared with other institutions, and 92% expressed satisfaction with the training. As a follow-up, a seminar on teaching materials will be organized in Southern Thailand.